Design and Validation of the Primary-Secondary School Transitions Emotional Wellbeing Scale (P-S WELLS); the First Scale to Assess Children's Emotional Wellbeing in the Context of Primary-Secondary School Transitions - Bagnall, Charlotte Louise; Jindal-Snape, Divya; Panayiotou, Margarita; Qualter, Pamela (International Journal of Educational and Life Transitions, 2024)
Children with poor emotional wellbeing and mental health, following primary-secondary school transitions, are more likely to experience increased educational disruption, poor academic attainment, and social maladjustment, which can lead to poor life chances and exacerbate existing social inequalities. However, the corpus of scales used to assess primary-secondary school transitions and emotional wellbeing during this time have considerable limitations, which has significant consequences for identifying and supporting children’s emotional wellbeing at this critical juncture.Outlined is a protocol for the design and validation of the first robust, sensitive, and standardised accessible scale, to longitudinally assess children’s emotional wellbeing in the context of primary-secondary school transitions. This brief and accessible scale will be named the Primary-Secondary School Transitions Emotional Wellbeing Scale (P-S WELLS). P-S WELLS will be developed following a multi-informant, mixed-methods model of scale development, which we outline to facilitate transparent reporting.The lack of a standardised, robust, sensitive, and accessible quantitative scale to assess children’s emotional wellbeing, over time and in the context of primary-secondary school transitions, is inhibiting empirical progress within the field, our ability to best support children in practice, and likely leading to policies and practices that are not fit for purpose. P-S WELLS and its development will be novel in its (a) approach, in that we will ask children about their feelings towards the changes they are negotiating in context; (b) use longitudinal design and operationalisation; and (c) aim to overcome limitations found in previous work.
Keywords: primary-secondary school transitions; emotional wellbeing; scale development; children; protocol; Delphi method; co-production